2023
DOI: 10.3390/medicina59010168
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Comparing Insertion Torque and Implant Stability of Two Different Implant Macrogeometries in the Initial Periods of Osseointegration

Abstract: Objectives: The present study compared two implants with different macrogeometries placed in healed alveolar sites, evaluating the insertion torque (ITV) and implant stability quotient (ISQ) values at three different periods. Methods: Seventy patients with a total of 100 dental implants were allocated into two groups (n = 50 per group): DuoCone implants (DC group) that included 28 implants in the maxilla and 22 in the mandible, and Maestro implants (MAE group) that included 26 in the maxilla and 24 in the mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Subsequently, Lekholm & ZARB (1985) proposed a classification aimed at quantifying the bone defects present in the alveolar ridge, as well as their quality. Regarding this last factor, the authors described four types of alveolar ridges, ranging from those that were totally corticalized to those where there was a predominance of medullary bone, as follows: Type A, virtually intact alveolar ridge; Type & MEREDITH, 1998;NEDIR et al, 2004;NOGUEROL et al, 2006;DILEK et al, 2008;CHO et al, 2009;SEONG et al, 2009;GEHRKE et al, 2019;DI STEFANO et al, 2019;ATIEH et al, 2021;ELIAS & SOARES 2021;GEHRKE et al, 2023). In relation to implants, primary stability depends on different macrogeometric characteristics, in the composition and treatment of their surface, and one or more of these characteristics increase the biological response of the tissue on the implant surface, leading to an increase in the success or survival rate (MEREDITH, 1998;SANTOS et al, 2013;PONZONI et al, 2018;DI STEFANO et al, 2021;ELIAS & SOARES, 2021;GEHRKE et al, 2023).…”
Section: Alveolar Atrophiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Lekholm & ZARB (1985) proposed a classification aimed at quantifying the bone defects present in the alveolar ridge, as well as their quality. Regarding this last factor, the authors described four types of alveolar ridges, ranging from those that were totally corticalized to those where there was a predominance of medullary bone, as follows: Type A, virtually intact alveolar ridge; Type & MEREDITH, 1998;NEDIR et al, 2004;NOGUEROL et al, 2006;DILEK et al, 2008;CHO et al, 2009;SEONG et al, 2009;GEHRKE et al, 2019;DI STEFANO et al, 2019;ATIEH et al, 2021;ELIAS & SOARES 2021;GEHRKE et al, 2023). In relation to implants, primary stability depends on different macrogeometric characteristics, in the composition and treatment of their surface, and one or more of these characteristics increase the biological response of the tissue on the implant surface, leading to an increase in the success or survival rate (MEREDITH, 1998;SANTOS et al, 2013;PONZONI et al, 2018;DI STEFANO et al, 2021;ELIAS & SOARES, 2021;GEHRKE et al, 2023).…”
Section: Alveolar Atrophiesmentioning
confidence: 99%
“…As a result of bone remodeling and biological fixation in the BIC, there is a process of osseointegration, establishing secondary stability. Therefore, the factors related to implant stability are bone quality and quantity, surgical technique, and bioengineering, which can influence the implant activation time for each individual situation (LIAJE et al, 2012;BALDI et al, 2018;DI STEFANO et al, 2021;MELLO-MACHADO, 2021;ELIAS & SOARES 2021;GEHRKE et al, 2023).…”
Section: Health Of Tomorrow: Innovations and Academic Researchmentioning
confidence: 99%
“… 22 A randomized controlled trial by Gehrke et al to evaluate the influence of dental implant macro geometry on early stability found that modifications of implant macro geometry produced significant reduction in the insertion torque compared to conventional implant design. 23 Haseeb et al compared the implant stability and insertion torque of two different macro geometry in different bone densities and concluded that lower insertion torques of new implant types help in reducing failure. 24 Gandhi et al evaluated how two different implant designs responded to conventional osteotomy drilling and found that tapered pro implant design offered a better primary stability when osseodensification was used.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors are related to the increase in temperature during the osteotomy, such as drilling depth, drill design and sharpening, bone density, drilling speed, manual pressure applied, intermittent or continuous movements, and irrigation 14 17 . Gehrke et al 17 recently showed that bone healing is directly related to the trauma generated during the osteotomy and implant insertion torque 18 , 19 . The maintenance of adequate temperature levels can be achieved mainly with irrigation.…”
Section: Introductionmentioning
confidence: 99%